Atom locations in a Ni doped η-(Cu, Ni)6Sn5 intermetallic compound. (1st January 2019) - Yang, Wenhui; Yamamoto, Tomokazu; Aso, Kohei; Somidin, Flora; Nogita, Kazuhiro; Matsumura, Syo
Abstract: The present study has succeeded in direct determination of the location of dopant Ni atoms in η -(Cu, Ni)6 Sn5 by aberration-corrected scanning transmission electron microscopy (STEM) including atomic-resolution imaging as well as elemental mapping by X-ray energy-dispersive spectroscopy (XEDS). The three sublattices of Sn, Cu1 and Cu2 were distinguished in atomic-resolution images observed along the [ 2 1 ¯ 1 ¯ 0 ] direction. Atomic-resolution XEDS maps have verified for the first time that the dopant Ni atoms located at the Cu2 sites in η -(Cu, Ni)6 Sn5, taking advantage of the Poisson non-local principal component analysis (NLPCA) processing and the lattice-averaging procedure. Graphical abstract: Unlabelled Image